2002
DOI: 10.1097/00007890-200208270-00020
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of immunization for pre- and post- liver transplant children

Abstract: Although 12 of 58 patients (21%) had an infection, pretransplantation immunization was effective to prevent serious illness, especially for the 6 months after transplantation. Posttransplantation live-vaccine administration under immunosuppressive conditions is effective and safe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
139
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(145 citation statements)
references
References 18 publications
4
139
1
1
Order By: Relevance
“…The rates of protective antibodies in our patients are significantly lower than the other studies; Balloni et al found rates of 86.2% for diphtheria and 100% for tetanus in their study (12). Also Kano et al found the rates of seroconversion against measles, rubella, and mumps after pre-transplantation vaccination 82%, 100% and 95% respectively (13). Worns et al documented that seventy-six percent of the vaccinated patients with autoimmune liver disease (against HBV vaccine) developed anti-HBs antibody (14).…”
Section: Discussioncontrasting
confidence: 64%
“…The rates of protective antibodies in our patients are significantly lower than the other studies; Balloni et al found rates of 86.2% for diphtheria and 100% for tetanus in their study (12). Also Kano et al found the rates of seroconversion against measles, rubella, and mumps after pre-transplantation vaccination 82%, 100% and 95% respectively (13). Worns et al documented that seventy-six percent of the vaccinated patients with autoimmune liver disease (against HBV vaccine) developed anti-HBs antibody (14).…”
Section: Discussioncontrasting
confidence: 64%
“…The following provides further support for the safety of MV-Edm as a viral agent: (1) liver toxicity was not observed in CD46-positive mice and squirrel monkeys treated systemically with MV-Edm (S. J. Russell, personal communication); (2) the attenuated Edmonston vaccine strain has successfully been used for vaccination with an excellent safety profile; (3) reports of wild-type measles virus-induced hepatic damage are extremely rare or have failed to show the intrahepatic presence of the measles virus 55,56 ; and (4) posttransplant measles vaccination of patients who have undergone liver transplantation does not result in significant complications and is considered safe. 57,58 The observation that CD46 expression is increased in cirrhosis, though still 3 times lower than in HCC, indicates clinical phase I toxicity studies are necessary. 43,52 In addition, our previous data showed that intraperitoneal treatment of Ifnar ™ -CD46Ge transgenic mice with MV-GFP did not result in significant transgene expression, despite the presence of MV-Edm RNA in liver tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Seroconversion rates were higher in patients who had received measles vaccine before transplant (85%) as compared to children immunized only after transplantation (41%). Similarly, sustained immunity was observed in 64% of the patients previously vaccinated in comparison to 29% of the patients who were vaccinated only after transplantation 54,66,84 .…”
Section: Use Of Measles Vaccine In Special Circumstancesmentioning
confidence: 83%